Analysis of the Performance of Cutting Edge Addition on the PC 200 Bucket in Optimizing the Cleaning and Collecting Area of Coal in the Girimulya Pit - Marlina, Marlina; Nasution, Roy Nastigor (Doctoral Program of Social Science Pasundan University, 2025)
Improving efficiency in the coal area cleaning process is a key factor in enhancing productivity and reducing operational costs in the mining industry. In practice, challenges often arise due to the large coverage area of the pit, which requires several excavators with cutting buckets or standard buckets that travel long distances, consuming a significant amount of time, leading to lost time due to travel between these units. This study aims to analyze the performance of adding cutting edges to the bucket as an effort to optimize cleaning in coal areas. The research method involves field experiments by testing buckets equipped with cutting edges and measuring their effectiveness and efficiency compared to standard buckets. Data was collected through direct observations, interviews with heavy equipment operators, and an analysis of the time and operational costs before and after implementing cutting edges in the coal pit area of Kusan Girimulya Utara. The results of the study show that adding cutting edges to the bucket significantly improves the bucket's ability to lift and move materials, reduces the time required for the cleaning process, and decreases wear on the bucket. The addition of cutting edges also proves to reduce fuel consumption and maintenance costs, as well as improve work safety by reducing the potential for accidents due to a faster and more efficient cleaning process. In conclusion, the innovation of adding cutting edges to the bucket has a positive impact on optimizing the cleaning process in the coal area, improving operational efficiency, and reducing costs. This study recommends the widespread adoption of cutting-edge technology in the mining industry to achieve better productivity and performance.